Estimating the Criteria Affected to Agricultural Production: Case of Chau Thanh a District, Vietnam - Vu, Pham Thanh; Minh, Vo Quang; Nguyen, Phan Chi; Dung, Tran Van; Cuong, Nguyen The; Lan, Nguyen Thi Phong (Asian Journal of Agriculture and Rural Development, 2020)
The study aimed to assess the current agricultural production and to identify the criteria affecting the agricultural cultivation and overcome the limitations in agricultural production of Chau Thanh, A district of the Mekong Delta, Vietnam. The study collected primary from farmers using Participatory Rapid Appraisal tool, and discuss directly with experts and local agricultural managers. The results showed that economic development mainly based on agriculture (of which the paddy and fruit trees land were the most 13.577 ha (98,8%)). The five criteria were identified (techniques, physical, social, economic, and environment) and twenty-six sub-criteria, in which the production scale (0.084), infrastructure (0.071), total income (0.075) and profit (0.062) were the most important factors. The AHP analysis assisted in proposing several solutions such as infrastructure construction and non-structural solutions to cover the output of products to develop sustainable agricultural production. Therefore, the case study of Chau Thanh A district was used to support the development of agriculture production.